Decolonization and the Cold War - Robert McMahon (Master's Programs in International Relations, Faculty of Social and Political Science, Jenderal Achmad Yani University (UNJANI)., 2023)
Throughout the Cold War era, the United States and the Soviet Union frequently faced the dilemma of whether to recognize or to confer legitimacy upon armed insurgencies vying to overturn established civil authority. The superpower conflict, at once ideological and geopolitical, came to encompass the entire globe by the 1950s, with the Third World emerging as the chief zone of competition between the two superpowers–as well as the main source and site of non-state armed groups. The potential transformations of these armed groups into governments threatened to alter the prevailing balance of regional and global power. Policymakers in Washington and Moscow, consequently, needed to calculate carefully how the granting of de jure or de facto recognition to a particular armed insurgency, or the accordance of some form of legitimacy to it, might affect broader Cold War goals. Why did the United States and the Soviet Union, this essay asks, choose to recognize some insurgencies, deny recognition to others, and actively oppose still others? How, for their part, did these various armed, non-state actors seek to gain support, recognition, and legitimacy from one, or both, of the superpowers? What factors best explain their relative successes or failures in those endeavors? the present article explores those larger questions by focusing specifically on armed decolonization movements, arguably the most common and most consequential of the non-state, armed groups that emerged throughout the post-1945 period. In each of the cases examined here, the superpowers sought to shape the outcome of the decolonization struggle, offering, or withholding military support and diplomatic recognition as a weapon of influence. In each case, the aspiring national liberation movement deployed a combination of armed strength and diplomatic advocacy in a bid for legitimacy and recognition, seeing the support of one or both superpowers as instrumental to the overarching goal of full-fledged sovereignty and acceptance within the prevailing international state-based system.